Projeto de fixação de absorvedor de impactos acoplado ao chassi de caminhão para transporte de bombas anfíbias em terreno de mina - BARROS JUNIOR, Cloves Augusto Coelho (2024)
Vibration isolation is essential to prevent wear and failure in machines by focusing on reducing vibration transmitted from the base to the machine. Reducing the vibration suffered by a submersible pump during transport on mine land means extending its useful life and reducing maintenance costs. The project seeks to meet this need with objectives such as the selection of shock absorbers, mechanical tests, modeling for computer simulations and evaluation of post-installation vibration behavior. Based on the bibliographies and using the finite element method (FEM), the project begins, generating the 3D model of the system components and making adjustments to the models, if necessary, for simulations in finite element software. The cushion that meets the project requirements was selected, and the stiffness and modulus of elasticity were subsequently obtained in laboratory compression tests. Equivalent models were developed for the cushion and pump, adjusting dimensions and mass for accurate simulations. Under static load, the base presented satisfactory performance with small displacement, Von Mises equivalent stresses below the yield limit of a structural steel and the safety factor indicates suitability of the structure for the project. The first six vibration modes of the set coincided with translation and rotation movements with frequencies between 8.6334 and 33.173 Hz. The harmonic analysis revealed satisfactory performance in three points, contrasting with the previous rigidity of the system since the introduction of an elasticity element reduced vibration transmission. In the transient analysis, the system was shown to be underdamped with a reduction in damping and spring forces over time, tending to zero, in accordance with vibration theories. The addition of a damper system to the pump clearly indicates benefits to the health of the machine, reducing maintenance interventions and saving costs for the company.